Transarterial radioembolization: a systematic review on gaining control over the parameters that influence microsphere distribution - T. J. Snoeijink; T. G. Vlogman; J. Roosen; E. Groot Jebbink; K. Jain; J.F.W. Nijsen (Taylor & Francis Group, 2023)
Abstract[Purpose] Transarterial radioembolization (TARE) is an established treatment modality for patients with unresectable liver cancer. However, a better understanding of treatment parameters that influence microsphere distribution could further improve the therapy. This systematic review examines and summarizes the available evidence on intraprocedural parameters that influence the microsphere distribution during TARE as investigated by in vivo, ex vivo, in vitro and in silico studies. [Methods] A standardized search was performed in Medline, Embase and Web of Science to identify all published articles investigating microsphere distribution or dynamics during TARE. Studies presenting original research on parameters influencing the microsphere distribution during TARE were included. [Results] A total of 42 studies reporting a total of 11 different parameters were included for narrative analysis. The investigated studies suggest that flow distribution is not a perfect predictor of microsphere distribution. Increasing the injection velocity may help increase the similarity between flow and microsphere distributions. Furthermore, the microsphere distributions are very sensitive to the radial and axial catheter position. [Conclusion] The most promising parameters for future research which can be controlled in the clinic appear to be microsphere injection velocity as well as the axial catheter position. Up to now, many of the included studies do not take clinical feasibility into account, limiting the translation of results to clinical settings. Future research should therefore focus on the applicability of in vivo, in vitro, or in silico research to patient specific scenarios to improve the efficacy of radioembolization as treatment for liver cancer.